Assessment of communication skill during process of preoperative visit and informed consent by anesthesiology residents - Sweta V Salgaonkar; Aarti D Kulkarni; Sunil P Chapane (Wolters Kluwer Medknow Publications, 2021)
Background and Aims: Anaesthesiologists have few opportunities to communicate with patients especially in preoperative period for various reasons. If these opportunities are not well utilized, anesthesiologists may not be able to educate patients about anaesthesia related issues. The aim of this study was to assess communication skill (CS) exhibited by the anesthesiology residents during the process of preoperative visit and informed consent. Material and Methods: This was a pre and post intervention questionnaire based study carried out in a presurgical ward of a tertiary hospital. During the process of preoperative visit and informed consent, fourteen of the second year anesthesia residents were assessed by faculty members for various aspects of CS using validated questionnaire on 3-point Likert's scale, before and after CS workshop. Residents' perception about workshop and patient satisfaction with regards to the preoperative visit and process of informed consent was assessed. Results were described in percentage value and a qualitative analysis was carried out. Results: While none of the residents exhibited 'excellent CS score' in the pre-workshop phase, six (42.86%) achieved the same after the workshop. One resident, who had 'poor CS score' moved to higher category score post workshop. The behavioural traits of professionalism, empathy, risk explanation and written consent showed statistically significant improvements post intervention by Wilcoxon Signed Rank Test, with P value < 0.05. All residents felt that good communication can improve patient satisfaction and CS training should be part of the post graduate curriculum. Conclusion: Conduct of CS workshop for anesthesia residents improved certain behavioral traits during anaesthesia preoperative visit and informed consent process. This important nontechnical skill of CS, may not be uniformly acquired during clinical training and should be specifically taught and evaluated as part of post graduate curriculum.